PENGARUH CEKAMAN AIR DAN PEMBERIAN PUPUK DAUN TERHADAP PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Nurjanaty, Netty; Linda, Riza; Mukarlina, Mukarlina (Jurnal Protobiont, 2019)
The availability of water for plants will affect the process of plant growth. Water stress in plants can be overcome by applying fertilizer. Fertilizing through leaves has the advantage of absorbing nutrients needed to speed up the growth process. The purpose of this research was to use a completely randomized design (CRD) with two factors, namely the A factor of water supply consisting of 100% field capacity (KL) (A1), 75% KL (A2), 125% KL (A3), B concentration factor leaf fertilizer consists of 0 g/L (B1), 1,5 g/L (B2), 2 g/L (B3), 2,5 g / L (B4), and 3 g/L (B5) so that there is 15 combinations of treatments with 5 replications. Based on the results of research on the stress conditions of 75%, 100%, and 125% KL the best leaf fertilizer for growth of mustard green plants which includes leaf area, amount of chlorophyll, number of leaves, wet weight, dry weight, and root-shoot ratio is as much as 3 g/L.